“Playing poop”: an interesting case of bird dropping masquerade in leafmining Buprestidae (Agrilinae, Tracheini) - Migliore, Letizia J.; Curletti, Gianfranco; Giulio, Andrea Di; Ruzzier, Enrico (Zootaxa, 2025)
The present contribution discusses the possible defensive camouflage strategy adopted by Leiopleura venustula (Gory, 1841), a South American leafmining buprestid beetle (Buprestidae, Agrilinae, Tracheini). This species presents a coloration pattern resembling older dry bird droppings and displays the capability to secrete a large amount of highly convoluted wax filaments on its dorsum. These filaments, specifically secreted by a series of pores present in the rough areas of pronotum and elytra, apparently improve the quality of the camouflage mimicking the (white) uric acid commonly found in bird faeces. SEM images of distribution of pores and wax filaments are presented.